Visual looting on the covers of international magazines (Al-Academy, 2023)
The strategy of designing the covers of international magazines emerges as one of the expressive means that reflect the emotional and expressive aspects and employ them according to the spatial transformations and the struggles of globalization to usurp the intellectual, cultural, value and civilizational essence of man, which makes him vulnerable to psychological and spiritual alienation and becomes the abstract meaning of identity and culture, and the empowerment of cultural invasion and the control of consumer thought The contemporary globalist on the largest area and the globalization of the peoples of the world, and the study came in the first chapter: the general framework that includes the problem of the research to raise in our mind the following question: (What is the alienation of the visual in the design of the covers of international magazines?), The importance of the research lies in the study of the features of cultural, religious, political and social expression In the covers of contemporary international magazines and making their global covers a visual message related to cultures and values of authenticity and civilizational race at the global level. The aim of the study was to identify visual usurpation in the covers of international magazines. Alienation through the design idea) with indicators, and the third chapter included procedures The research and how to choose the research community and analyze sample forms, and the most important conclusions:1- International magazines raise topics that raise controversy towards political, cultural, religious, moral and aesthetic alienation, through design elements as visual alienation that raises ideas and questions in the imagination of the recipient and the reader.2- The covers of international magazines seek to be a means of visually alienating their design content by supporting different aspects that contribute to strengthening the material presented towards a self-visual culture that competes with globalized perspectives.